Vozes divergentes? Uma análise de gênero das opiniões sobre assuntos públicos no Brasil - Pereira, Shirley de Jesus Oliveira (2024)
This work aims to answer the following research question: Do men and women have the same opinions on public issues in Brazil? To do this, it was necessary to make a comparison between the female and male categories. The answers given by men and women on certain public issues in public opinion survey questionnaires that had already been carried out were analyzed. Two questionnaires were selected, Brazilian Electoral Study (ESEB/CESOP) 2022 and Latin American Public Opinion Project (LAPOP) 2018/2019. The work’s hypothesis is that women will have more progressive attitudes than men in relation to issues of compassion and more conservative attitudes in relation to moral issues. The public issues investigated were: social welfare policies, minority rights, equal roles between men and women, support for democracy and moral issues. The independent variables were: sociodemographic, government evaluation, ideology, party preference, employment status, gender identity and number of children under 13 years old living in the house. After logistic and linear regression analyses, it was found that Brazilian women tend to support the adoption of children by a gay couple and same-sex marriage more than men (support appears both in the ESEB data and in the LAPOP data) and the rights of homosexuals to run for public office, that public schools teach children to pray and believe in God. They opposed the decriminalization of drug use, the reduction of the age of criminal responsibility, privatization of public service, the fact that the rich pay a lot of taxes and receive little in state services and abortion even in cases where the mother's life is at risk. They are less likely to believe that democracy is preferable to other forms of government and are more dissatisfied with democracy in the country than men (similar results in both ESEB and LAPOP data).